ความสัมพันธ์ระหว่างสุขภาวะด้านจิตวิญญาณของพยาบาลและการดูแลผู้ป่วย ด้านจิตวิญญาณ THE RELATIONSHIP BETWEEN NURSE’ SPIRITUAL WELL-BEING AND THEIR SPIRITUAL CARE - โพยนอก, สุกัญญา; เหลืองอ่อน, ดวงรัตน์; บุญอุไร, สุวภา; ทองสุข, พิทักษ์; วัฒนพฤกษ์, ภาสกรณ์ (Srinakharinwirot University Journal of Sciences and Technology, 2021)
The nurse’ spiritual well-being is very important. Because it affects the care of patients, That is, having a good spirit results in the nurse being aware of the spiritual needs of the patient. Making it possible to take care of patients in the spiritual dimension well. The purpose of this study were to examine predictors of spiritual well-being on their spiritual care. The assessments included a spiritual well-being questionnaire on 5 level rating scale, consisting of 3 parts: general information, spiritual health of nurses, CVI equal to 0.940, confidence value equal to 0.925, and spiritual care, CVI equal to 0.88, confidence value 0.940. One hundred and twenty-two nurses from Panyananthaphikkhu Chonprathan Medical Center Srinakharinwirot University were recruited. Data analysis using linear regression and analysis of variance. The results revealed that most of the sample groups were female, 95.9%, single status 63.1%, Buddhism 95.9%, graduated bachelor degree 92.6%, age from 22-60 years old, mostly age 26-30 years, 32%. Work experience found that most of the work from 1-41 years old, most of the work is over 10 years, accounting for 42.6%, followed by the group of workers age 1-5 years, accounting 35.2%. Workplaces found that most of them work in General ward, 41.8%, followed by those work in intensive care units accounting for 24.6%. The sample reported having moderate level of spiritual well-being, 3.888 (S.D. = 0.435 and their spiritual care was at a moderate level, 3.172 (S.D. = 0.601). The relationship between nurse’ spiritual well-being and their spiritual care it was found that only the 3rd element, meaningful life could explain the spiritual care significantly .05 (p-value = .012), by explaining for spiritual care by 5.1 percent. In addition, the experience of caring for family members who were in the end of life had resulted in the nurse’ spiritual well-being were significantly different at the level of .05 (p-value = .035. Conclusion: The third element of the nurse’ spiritual well-being is having a meaningful life. There was a significant positive correlation with the spiritual care for patients.